PEMBELAJARAN BERBASIS PjBLTERINTEGRASI TRI N PEMBUATAN ECOBRIK UNTUK MENINGKATKAN DIMENSI KREATIF DAN GOTONG ROYONG - Novita Sakti Dewanti; Insanul Qisti Bariyah (Jurnal Muara Pendidikan, 2024)
Application of learning models that are less than optimal when learning activities take place can result in a lack of a sense of mutual cooperation among students, in addition to resulting in students being less able to develop their creative attitudes. Because in conventional learning, learning is teacher-centered. One learning model that can be used to increase students' creative and mutual cooperation dimensions is by using the Project Based Learning (PjBL) learning model because this PjBL model is a student-centred learning model and can produce a project. The method used in this research is a qualitative descriptive method. This research aims to improve students' creative attitudes and also increase the sense of mutual cooperation with friends through ecobrik-making activities. In this research, there are 6 stages of learning in the Project-based Learning (PjBL) model. Of the six activity stages, there were 4 stages that got very good results and 2 stages that got good results. In the mutual cooperation dimension, maximum results are obtained because the activity of making eco-bricks requires an attitude of cooperation between students and each other. The creative dimension still needs to be improved. The subjects of this research were fourth-grade students at one of the elementary schools in Sleman Regency. In this ecobrik-making activity, it is hoped that they can slightly reduce or deal with the waste in the environment around them, both in the school environment and the home environment. This is in accordance with Ki Hajar Dewantara's teachings, namely Tri N, Niteni, Nirokke, and Nambahi. Niteni, namely, students understand the explanation that has been given by the teacher, nirokke, students can do things that have been conveyed and taught previously by the teacher and addition, namely, students can add to the results that have been made earlier by adding creativity from students